The Failure of Hizbut Tahrir Indonesia’s Strategy in Establishing Khilafah: Advice for the Government Policies - Al Amin, Ainur Rofiq; Zaki, Irham; Zusak, M Bastomi Fahri; Hosen, Nadirsyah (Journal of Al-Tamaddun, 2025)
The objective of this study is to analyze the shortcomings of Hizbut Tahrir Indonesia’s strategy in establishing an Islamic caliphate within the country. This research employs a qualitative approach through content analysis and field studies, which include interviews with prominent figures associated with Hizbut Tahrir Indonesia (HTI) activities. The findings indicate that while HTI executed all phases of their strategy, they ultimately failed to establish a caliphate in Indonesia, concomitant with their decline in presence within the nation. This failure can be attributed to the significant rejection of the caliphate concept by the majority of Islamic community organizations in Indonesia. Furthermore, HTI’s strategy exhibited a lack of depth, as evidenced by a conceptual inconsistency between their approach and divine promises. This research opens avenues for future inquiries into HTI’s physical political movements and their systemic implications. Additionally, it elucidates the manner in which HTI implemented each stage of their strategy and provides insights into the reasons behind their inability to establish the caliphate. The study aims to enhance public awareness regarding the strategies employed by Islamic political groups operating in Indonesia. From a social perspective, the findings serve as reference material for political policies in Indonesia, particularly concerning transnational ideologies that have gained traction in recent decades. Previous studies have failed to adequately explore the execution and outcomes associated with HTI’s strategic implementation; this study specifically addresses the deficiencies in HTI’s strategy execution.